Men and type 2 diabetes: how everyday knowledge remains unshared in gendered medical encounters - Louise Søgaard Hansen; Anne-Louise Bjerregaard; Peter Bindslev Iversen; Nicole Thualagant (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Managing everyday life with type 2 diabetes can be challenging. In particular, men considered vulnerable are often portrayed as lacking self-management. This paper challenges this assumption by highlighting the unheeded knowledge and self-care practices these men develop, and by exploring how these are included in healthcare encounters at an outpatient clinic in Denmark. Methods Data were collected through observations of clinical practice and subsequent interviews with 12 men who have type 2 diabetes. A thematic analysis was conducted to explore their daily experiences of managing chronic illness and their encounters with healthcare professionals. Results Men considered vulnerable manifest important knowledge and strategies in managing type 2 diabetes in their daily lives, often perceiving the illness as barely present. Their encounters with healthcare professionals, particularly females, often draw on repertoires from previous experiences with (often female) care professionals and seem to follow a certain script for (female) carers encountering disadvantaged (male) care recipients. These dynamics frequently overlook the men’s lived experiences and self-management knowledge. Conclusion Men considered vulnerable develop important coping strategies and knowledge for managing type 2 diabetes in their everyday lives. However, their encounters with health professionals often perpetuate gendered assumptions and exclusion of their everyday experiences and knowledge.